2011
DOI: 10.1159/000323806
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Status of Imprinted Genes and Repetitive Elements in Sperm DNA from Infertile Males

Abstract: Stochastic, environmentally and/or genetically induced disturbances in the genome-wide epigenetic reprogramming processes during male germ-cell development may contribute to male infertility. To test this hypothesis, we have studied the methylation levels of 2 paternally (H19 and GTL2) and 5 maternally methylated (LIT1, MEST, NESPAS, PEG3, and SNRPN) imprinted genes, as well as of ALU and LINE1 repetitive elements in 141 sperm samples, which were used for assisted reproductive technologies (ART), including 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 94 publications
10
94
0
6
Order By: Relevance
“…In any case, according to the clinical data at our disposal, our results coincide with the four studies published to date, 19,22,25,47 in which no evidence was found that these anomalies affect the results of assisted reproduction treatments.…”
Section: -supporting
confidence: 89%
See 1 more Smart Citation
“…In any case, according to the clinical data at our disposal, our results coincide with the four studies published to date, 19,22,25,47 in which no evidence was found that these anomalies affect the results of assisted reproduction treatments.…”
Section: -supporting
confidence: 89%
“…Even though the reported epidemiological data lead one to consider maternal methylation defects exclusively, a relationship between male infertility and imprinting abnormalities in the sperm has also been described. [18][19][20][21][22][23][24][25][26] Since paternal imprinted genes mainly contribute to extra-embryonic tissue development, it is not discarded that loss of imprinting (LOI) at paternal methylated loci could cause phenotypes that prevent placenta development or could cause intrauterine growth retardation (IUGR). IUGR has been described as being associated with imprinting defects 8 and also related to assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…About 35% of the issues involved with infertility are due to the man, another 30% due to the woman, and 10% result from complications associated with both partners [1]. There are many causes of infertility, however, approximately 30% of cases are associated with genetic factors such as translocations [2].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of a proper methylation at specific gene promoters is required for an appropriate sperm function and aberrant methylation patterns have been associated with infertility and poor sperm quality in men (Jenkins and Carrell 2012b;Jenkins and Carrell 2012a;Houshdaran et al 2007). Moreover inappropriate methylation status has been suggested to be related with recurrent pregnancy loss (El Hajj et al 2011). …”
Section: The Importance Of Chromatin Methylationmentioning
confidence: 99%